2020
DOI: 10.1002/cbf.3602
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and mesenchymal stem cells derived exosomes: Molecular insight and challenges

Abstract: Ageing induces a great risk factor that participates in progressing various degenerative diseases morbidities. The main characteristic of ageing is the failure in maintaining homeostasis in the organs with a cellular senescence. Senescence is characterized by reduced cell growth, evade cellular death, and acquiring a senescence‐associated secretory phenotype (SASP). Mesenchymal stem cells (MSCs) are advantageous cells in regenerative medicine, exerting pleiotropic functions by producing soluble factors, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 83 publications
(97 reference statements)
0
55
0
Order By: Relevance
“…Rezaie et al reported MSCs and their exosomes kinetic are affected by aging and other aged exosomes. Exosomes from aged MSCs lose their regeneration potential, accelerating biological development and negatively impacting the function of recipient cells ( 69 ). Choosing an appropriate pathway for exosomes to access target sites is another issue that needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Rezaie et al reported MSCs and their exosomes kinetic are affected by aging and other aged exosomes. Exosomes from aged MSCs lose their regeneration potential, accelerating biological development and negatively impacting the function of recipient cells ( 69 ). Choosing an appropriate pathway for exosomes to access target sites is another issue that needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Due to MSCs lack the expression of membrane bound molecules involved in immune rejection which enable their allogenic transplantation, the clinical applications of MSCbased therapy have witnessed an outstanding achievement (Ahmadi and Rezaie, 2021). Nevertheless, in the long-term follow up, safety issues regarding MSCs-based therapy are still a matter of debate.…”
Section: Evs-based Covid-19 Therapy Msc and Msc-evsmentioning
confidence: 99%
“…Exosomes serve as a new therapeutic target and could act as a biomarker for various disorders including cardiac disease ( 190 ). Mesenchymal stem cell derived exosomes (MSC-exo) used for various aging related diseases ( 192 ).…”
Section: Stem Cellsmentioning
confidence: 99%